2016
DOI: 10.1126/sciadv.1600261
|View full text |Cite
|
Sign up to set email alerts
|

Direct proof of spontaneous translocation of lipid-covered hydrophobic nanoparticles through a phospholipid bilayer

Abstract: Spontaneously translocating lipid-coated hydrophobic gold nanoparticles open doors for new biotechnology applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
136
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(146 citation statements)
references
References 58 publications
8
136
1
1
Order By: Relevance
“…The propensity of biological species to form coronas around nanoparticles [1][2][3][4][5] has been used for preparing engineered nanomaterials that can be distributed in biological systems with some control. [6][7][8][9][10][11] Although protein coronas in particular have been studied extensively, 1-3,6,7 our understanding of lipid coronas is now just beginning to emerge, [12][13][14][15] especially of those formed upon unintended nanoparticle contacts with living cells. The protein and lipid corona formation mechanisms appear to differ substantially, as ''hard'' and ''soft'' coronas, 16 typical for the former, have not been described for the latter.…”
Section: Introductionmentioning
confidence: 99%
“…The propensity of biological species to form coronas around nanoparticles [1][2][3][4][5] has been used for preparing engineered nanomaterials that can be distributed in biological systems with some control. [6][7][8][9][10][11] Although protein coronas in particular have been studied extensively, 1-3,6,7 our understanding of lipid coronas is now just beginning to emerge, [12][13][14][15] especially of those formed upon unintended nanoparticle contacts with living cells. The protein and lipid corona formation mechanisms appear to differ substantially, as ''hard'' and ''soft'' coronas, 16 typical for the former, have not been described for the latter.…”
Section: Introductionmentioning
confidence: 99%
“…At the mesoscale (characteristic length ∼ 100 nm) , experimental studies have largely focused on the biodistribution of functionalized NPs, targeted to various cellular adhesion molecules both in vitro and in vivo, for use as targeted drug delivery systems [29][30][31][32][33][34][35][36]. A number of theoretical and computational models [37][38][39][40][41][42][43][44][45][46][47][48][49][50] have been developed to address the question of adhesion and super-selective targeting of functionalized NCs and their uptake into the target cell [51][52][53][54][55][56]. At the molecular scale (characteristic length < 20 nm), all atom molecular dynamics simulations have been extensively used to unravel the molecular mechanisms governing receptor-ligand interactions [57][58][59][60][61] and the interaction of gold and silver nanoparticles with the surface of a cell [62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…This observation is in agreementw ith previous studies on lipid-coatedh ydrophobic Au NPs of 5nm, which demonstrated that hydrophobic NPs with diameter d > 5nmt ranslocate through the bilayer,w hereas individual NPs with d 5nma re trapped in the bilayer.T he only possibility of small hydrophobic NPs for leaving the bilayer is by forming clusters exceeding the threshold size. [36] Based on our previous work, we know that the QD_F form nanoclusters in aqueous media containing only 5% of DMSO. [37] Therefore our hypothesis is that these hydrophobic QDs, both QD_F and QD_TOPO, cross the cell membrane as clusters.…”
mentioning
confidence: 99%